THE DEVELOPMENT OF LEMON PRODUCTS INTO FRUIT JUICE IS BASED ON THE LEVELS OF VITAMIN C AND pH BASED ON COOKING TEMPERATURE - Yan El Rizal Unzilatirrizqi; Rois Nurlatifah (Institute of Computer Science (IOCS), 2023)
Vitamin C is a type of water-soluble vitamin that is susceptible to heating. The aim of this study was to determine the effect of vitamin C content on heating temperature and the effect of storage time on the pH level of lemon juice. The method used in this study was a completely randomized design with 5 treatments at a temperature variation of 0°C, 60°C, 70°C, 80°C, and 90°C and pH measurements at 4 days of storage. The vitamin C content of a lemon juice before processing is 4.7861%. According to research findings, the most appropriate product is heating at a temperature of 70-800 °C with a pH ranging from 2.3 to 2.6 and no significant color change to the original hue of the juice.